The Impact of Oil Sector on the Global Competitiveness of GCC Countries: Panel Data Approach - Anas Al Qudah; Ahmed Badawi; Mostafa E. AboElsoud (Research Journal of Finance and Accounting, 2016)
This study explores the impact of oil sector on global competitiveness of the GCC states in a panel data framework for the period from 2006 to 2014. The focus is placed on how the non-traditional factors; oil rents, fuel exports as percentage of merchandise exports, oil prices, and mining sector production impact on the global competitiveness of the GCC nations. The study uses panel data techniques to measure the effect of the oil sector's impact on of global competitiveness of the GCC countries. The results of the regression show that the relation between rent and GCI found to be negative and highly significant whereas the oil prices and contribution of the mining sector in GDP found to have positive relation with GCI at 90% significance level. Finally, fuel exports as percentage of the merchandise exports has insignificant relation with GCI.
Keywords: E31; E37; F11; F14; 330; Oil Sector; Global Competitiveness; GCC Countries; Panel Data